Electrical, optical and far-field measurement of semiconductor light sources - Liu, Wei Feng. (2011)
In this report, we will touch on the characteristics of semiconductor laser devices, namely, their fundamental operations, implementations, background theories, requirements of semiconductor lasers and some useful equations. We will also discuss on the characteristics, advantages, applications and power description of a Quantam Cascade Laser (QCL) device. Finally we will discuss on the optimization of strain-balanced QCL structure (QCL design) and high power QCL performance improvement.